Worlds at war - Pagden, Anthony (Random House, 2008)
Includes bibliographical references (p. [583]-601) and index.; Perpetual Enmity -- In the Shadow of Alexander -- A World of Citizens -- The Church Triumphant -- The Coming of Islam -- Houses of War -- The Present Terror of the World -- Science Ascendant -- Enlightened Orientalism -- The Muhammad of the West -- The Eastward Course of Empire -- Epilogue: Towards the Future.